Drought and food security – Improving decision-support via new technologies and innovative collaboration - Enenkel, Markus; See, Linda; Bonifacio, Rogerio; Boken, Vijendra; Chaney, Nathaniel; Vinck, Patrick; You, Liangzhi; Dutra, Emanuel; Anderson, Martha (Elsevier, 2015)
Governments, aid organizations and people affected by drought are struggling to mitigate the resulting impact on both water resources and crops. In this paper we focus on improved decision-support for agricultural droughts that threaten the livelihoods of people living in vulnerable regions. We claim that new strategic partnerships are required to link scientific findings to actual user requirements of governments and aid organizations and to turn data streams into useful information for decision-support. Furthermore, we list several promising approaches, ranging from the integration of satellite-derived soil moisture measurements that link atmospheric processes to anomalies on the land surface to improved long-range weather predictions and mobile applications. The latter can be used for the dissemination of relevant information, but also for validating satellite-derived datasets or for collecting additional information about socio-economic vulnerabilities. Ideally, the consequence is a translation of early warning into local action, strengthening disaster preparedness and avoiding the need for large-scale external support.